Evaluation of fungicide application timing on soybean yield, quality, and economic return. Issue 1 (28th June 2021) - Floyd, Chase A.; Irby, J. Trenton; Allen, Tom W.; Catchot, Angus L.; Dodds, Darrin M.; Sarver, Jason M.; Maples, Will E.; Scholtes, Alanna B.; Carver, Shane M.
Abstract: The need for profitable soybean [ Glycine max (L.) Merr.] production practices grows as input costs rise and profit margins decline. In the mid‐southern United States, a prophylactic fungicide application at the initiation of pod development (R3 growth stage) is a common practice to protect yield potential in soybean. Experiments were conducted during 2017 and 2018 to determine optimal fungicide application timing in the absence of disease, while assessing multiple fungicide options and the resulting impact on soybean yield, quality, and partial return. Fungicide treatments included azoxystrobin as Quadris (Syngenta Crop Protection), azoxystrobin + difenoconazole as Quadris Top SBX (Syngenta Crop Protection), and the combination of fluxapyroxad + pyraclostrobin as Priaxor (BASF) and tetraconazole as Domark 230ME (Gowan). Fungicides were applied in single applications at R3 (three‐sixteenth‐inch long pod development), R4 (three‐fourth inch long pod development), R5 (beginning seed), or R6 (completely developed seed) growth stages or as two applications applied at R3 and again at R5. Based on results, soybean treated with Quadris Top SBX or Priaxor + Domark 230ME produced greater yield than non‐treated soybean. The growth stage when fungicides were applied did not influence soybean yield, confirming the value of current management strategies while also allowing flexibility in the application timing in situations that warrant application during later growth stages. These data suggest an application of Quadris Top SBX to soybean can protect yield while resulting in partial return at a market price of at least US$8.00 bu −1 . Adoption of prophylactic, multiplemode of action fungicide applications during fruiting development may sustain yields and improve net returns. Core Ideas: Timing of fungicide application did not affect soybean grain yield. Multiplemode of action fungicides improved soybean yield compared to no fungicide application. Application of fungicides increased overall seed mass, thus increasing yield. Quadris Top SBX generated the highest partial return at a selling price of US$8.00 per bushel.